Pendekatan Filosofis dalam Pengantar Pendidikan Kewarganegaraan di Perguruan Tinggi Berbasis Pembukaan UUD 1945 di Abad Ke-21 - Doni Ferdio I. D.; Devin Findi; Ihsan Setiaji Bagus Utomo; M. Hanif Amirudin; Renaldi Abdillah; Hidayat Nur Fikri; Ellyas Sugiharto; Andi Susanto; M. Faiquddin Putra; Suyono Suyono (Student Research Journal, 2024)
Technological developments and globalization have had a significant impact on civic education, so education policies need to be updated to be in line with the needs of modern society. This research aims to examine in depth the concepts, meanings, strategies, and insights of civic education in higher education through a philosophical approach to the Preamble to the 1945 Constitution in the context of the 21st century. The research was conducted using a descriptive method that utilizes observation, documentation, and literature studies that are comprehensively analyzed. The results of the study show that civic education based on a philosophical study of the Preamble to the 1945 Constitution can increase students' understanding of civic values in the context of contemporary Indonesia. This education is also a means of strengthening students' understanding of Pancasila and the 1945 Constitution as the basis of the state, with an emphasis on democracy, human rights, diversity, and national unity. In addition, this approach also underscores the importance of real practices, such as student participation in social and political activities, and the development of communication and leadership skills.